Work Environment and its Impact on Triple Constraint of Project Management - Raza, Syed Ali; ., Tamkeen Zehra Shah (Information Management and Business Review, 2012)
Project management’s fundamental concern is to effectively manage its triple constraints throughout the life cycle of a project to maximize productivity. At the same timework environment is considered a key feature, which influences the framework of project management. The present study assesses the impact of the work environment on the triple constraints (Scope, Time and Cost) of projects in the IT industry. The theoretical framework comprises Remuneration, Job Satisfaction, Job Security, and Working Hours as components of work environment and triple constraints as the dependent variable. Three hundred Project Managers across a number of IT firms have been approached, out of which 279 have responded to the questionnaire. The measurement tool has been developed by the researcher except for one construct, which has been adopted, followed by a pilot study. Inferential statistics have been applied to test the data. The study concludes that all project managers view a flexible and conducive work environment as bearing a strong relationship with the triple constraint of project management.